Towards (pro-)active intelligent products. (2018) - Wuest, Thorsten; Schmidt, Tim; Wei, Wei; Romero, David
Intelligent product research and applications are progressing rapidly. This development driven by the advances of ICT technology, product lifecycle focus, product-service systems (PSS), cloud computing, social network services, in short, the abundance of communication means and (user) data. Despite this rapid development, intelligent products are still rather passive in nature. In this study, we aim to investigate the future direction of intelligent products. The central research question is whether intelligent products are becoming more (pro-)active and/or socially active with subsequent questions regarding associated requirements and demands, barriers and challenges and information needs. To answer these questions, we conducted guided expert interviews and qualitative content analysis. The results indicate that the direction of intelligent products is moving towards a more (pro-)active future. We discuss how this new development is contributing to smart manufacturing as well as PSS design and operation and suggest an extension of two classification models for intelligent products.